The pathogenesis of infection with Trypanosoma vivax in goats and cattle - Masake, R.A. (1980)
Studies the pathology of Trypanosoma vivax in East African goats and Friesian cattle, with particular. ref. to goat & cattle parasitemia, susceptibility of goats over cattle in terms of higher parasitaemias, severe anaemia & death; describes major pathological changes occurring in lymph nodes, spleen, eyes, pituitary gland, testicles, heart, lung, liver & kidney.